2010
DOI: 10.1039/b927016g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of redox sensitive plutonium(iii) complexed with alkylated 2,6-ditriazinylpyridine (BTP) in organic solution

Abstract: Spectroscopic, solvent extraction methods and computational chemistry are applied for the characterization of redox sensitive trivalent plutonium complexed with the N-donor extracting agent alkylated 2,6-ditriazinylpyridines (n-C3H7-BTP) in organic solution. The redox stabilization and speciation of Pu(III) is discussed. Extraction of Pu(III) with n-C3H7-BTP is compared to that for redox stable Am(III). The speciation of Pu(III) with n-C3H7-BTP in organic solution is studied by UV-Vis/NIR and XAFS spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 21 publications
5
68
2
1
Order By: Relevance
“…The results agreed well with those in Ref. [31][32][33][34], which studied the coordination chemistry of Ce, Eu, Gd, Lu, U, Pu, Am, Cm onto n-C 3 H 7 -BTP in liquid-liquid extraction with four coordination shells model and the obtained R values of the first coordination layer were in the range of 250-262 pm. This result suggests that Dy(isobutyl-BTP/SiO 2 -P) 3 3?…”
Section: Adsorption Isotherm Of Dy(iii)supporting
confidence: 89%
See 1 more Smart Citation
“…The results agreed well with those in Ref. [31][32][33][34], which studied the coordination chemistry of Ce, Eu, Gd, Lu, U, Pu, Am, Cm onto n-C 3 H 7 -BTP in liquid-liquid extraction with four coordination shells model and the obtained R values of the first coordination layer were in the range of 250-262 pm. This result suggests that Dy(isobutyl-BTP/SiO 2 -P) 3 3?…”
Section: Adsorption Isotherm Of Dy(iii)supporting
confidence: 89%
“…The central metal ion Ce and the atomic number were changed into Dy and 66 respectively in feff.inp during the data process. During the data fitting, the EAXFS data of Dy(III) adsorbed on isobutyl-BTP/SiO 2 -P sample was modelled in a manner analogous to that of Ref [31][32][33][34]. using four coordination shells in the R-range of 1.2-5.5 Å .…”
mentioning
confidence: 99%
“…This is partially driven by the need for reliable radionuclide speciation methods to characterize processes and (geo-)chemistry determinant in the mobilization/immobilization of especially long-lived actinide nuclides necessary to reliably assess longterm safety of the disposal of nuclear waste stemming from nuclear energy production. Nuclear areas profiting from the use of SR characterization methods include topics in condensed matter physics and material science of the actinide elements, such as Pu containing superconductors, 1 issues related to stewardship of nuclear weapon stockpiles, 2 decommissioning of nuclear facilities, 3 cleanup procedures for contaminated land 4 and sectors of the nuclear fuel cycle, including ore mining, 5 fuel production, 6 fuel reprocessing, 7 waste disposal, 8 waste volume reduction, 9 waste conditioning, 10 of fissile nuclear materials. Countries like Germany favoring phasing-out nuclear power generation must meet the political and societal responsibility of promptly developing longterm safe disposal strategies for accumulated highly active, heat producing nuclear waste (HAW) in deep geological formations (retrievable or non-retrievable), to protect the biosphere and population from incalculable risks of ill-protected interim storage above ground.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that BTPs act as tridentate ligands, [10] forming 1:3 complexes with An III and Ln III in the solid state [10][11][12] and in organic solution. [6,[13][14][15][16][17][18][19]36,37] Titrations in organic phase [16,17] [16,17,19] We perform a comparative study on the complexation of Cm III and Eu III with nPr-BTP [2,6-bis(5,6-dipropyl-1,2,4-triazin-3-yl)pyridine] ( Figure 1) in water/methanol, 1:1. The formation of the respective BTP complexes is followed by time resolved laser-induced fluorescence spectroscopy (TRLFS).…”
Section: Introductionmentioning
confidence: 99%